Solution Synthesis, Processing, and Applications of Semiconducting Nanomaterials - Hsu, Julia W. P. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue covers solution synthesis, processing, and applications of non-metallic nanomaterials. Zhang et. al. and Jiang et. al. focus on synthesis of kesterite materials, and Wu et. al. and Zhang et. al. focus on synthesis of copper chromium oxide delafossite nanomaterials. Three of these papers discuss solar cell applications using these materials. Yun and Park's review paper explores the self-assembly of complex nanostructures. Bhalothia et al. show enhanced catalytic activity for NiOx@Pt nanostructures and Wu et. al. report high-sensitivity ammonia sensors made from SnO nanoshells. On flexible electronics, Nakamura et. al. developed Cu nitride ink for rapid photonic processing of conducting lines, Liu et. al. made Au/HfO2/Pt resistive random access memory devices, and Moreira et al. fabricated solution combustion oxide thin film transistors.